Combating Rheumatic Heart Disease in Pakistan: An Experience of Training, Screening and Community Outreach - Amna Zaheer (International Journal of Medical Students, 2025)
This experience outlines a training session conducted by Darul Qalb, a U.S.-based organization dedicated to eradicating Rheumatic Heart Disease (RHD) in low-income countries, in collaboration with HOPES, a student-run welfare organization at Karachi Medical and Dental College. The session aimed to equip medical students with essential skills to detect subclinical RHD using advanced portable ultrasound devices. Led by Dr. Ahmad Akhtar, the session introduced the Point-of-Care Ultrasound (POCUS) technique, a critical tool for assessing heart valve changes indicative of RHD. Through hands-on practice, participants, including myself, learned to effectively use ultrasound technology, which was later applied in a community outreach initiative where we screened children for RHD. Guided by experienced mentors, I identified cases of subclinical RHD, highlighting the importance of early detection in improving health outcomes. This experience demonstrated the powerful synergy of medical education, technology, and community outreach in combating RHD in resource-limited settings like Pakistan.